Lyme disease. - KONTOS (Β.Ι. ΚΟΝΤΟΣ), V. I.; ATHANASIOU (Λ. Β. ΑΘΑΝΑΣΙΟΥ), L. V. (Journal of the Hellenic Veterinary Medical Society, 2018)
Lyme borreliosis is a tickbone, zoonotic, chronic disease with multisystemic clinical signs caused by bacteria of borelia species. It has a worldwide distribution and it is transmitted by the ticks of ixodes species. The reservoir of the causative agent in nature are small rodents, wild mammals and birds. In man, the clinical picture is quite clear: the pathognomonic sign is the chronicum erythema migrans in the acute phase, while in the dog, the clinical picture is not as clear: it looks like that of lupus erythematosus. The most constant symptom is lameness caused by the affection of joints. Diagnosis is based on the detection of antibodies against borrelia by the IFA method. Concerning public health, it is mentioned that in the U.S and in northern European countries, it is the most frequent tickbone disease while in Greece only some sporadic cases have been reported.